(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
The fixation, as rigorous as possible, of ancient texts acquires maximum relevance in the case of languages which have long since disappeared, such as Lusitanian. The intense deterioration of certain areas of the epigraphic areas in inscriptions written in this language has divided the scientific community as to the reading of certain words contained therein, thus hampering the full understanding of such documents. The new “Morphological Residual Model” (MRM) technique, developed by one of the authors (HP) and now applied to the rock monuments of Cabeço das Fráguas and Lamas de Moledo, as well as to the stele of Arronches, offers objective and impartial results which make it possible to definitively clarify some of these doubts. Starting from this renewed and more exact fixation of the texts, we will not hesitate (J.C.R.) to draw, from now on, the appropriate interpretative conclusions.